FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK MOBIL DENGAN DIBERLAKUKANNYA PAJAK PROGRESIF DI KOTA SURAKARTA - Danarsi, , Siti Nurlaela , Hendro Subroto (Jurnal Akuntansi dan Pajak, 2017)
This study aimed to analyze the influence of the understanding, the tax rate, quality of service, awareness of taxation, tax penalties on tax compliance in paying car tax with the application of progressive tax in the city of Surakarta. This study uses a survey approach field (field research) through questionnaires convey to taxpayers car in Surakarta. Respondents are taxpayers who pay motor vehicle tax in SAMSAT Surakarta. The sampling is compulsory car tax imposed progressive tax rates .The sampling technique using random sampling with a sample of 30 respondents. Methods of data analysis using multiple linear regression test. These results indicate that: Understanding and Awareness of taxation no effect on tax compliance, while the tax rate, Quality of Service and Sanctions Tax effect on tax compliance.Keywords: Understanding, tax rates, quality of service, awareness of taxation, tax  penalties, tax compliance